Low vagal tone in two rat models of psychopathology involving high or low corticosterone stress responses. (March 2019) - Huzard, Damien; Ghosal, Sriparna; Grosse, Jocelyn; Carnevali, Luca; Sgoifo, Andrea; Sandi, Carmen
Highlights: Study rats lines selected for extreme, high or low, corticosterone responsiveness. High and Low corticosterone responsiveness lines have reduced vagal tone at rest. Extreme corticosterone responsiveness lines do not differ in sympathetic function. Abstract: The two stress-responsive physiological systems, autonomic nervous system (ANS) and hypothalamus-pituitary-adrenal (HPA) axis exert complementary and interrelated actions in the organism. Individuals that suffer stress-related psychopathologies frequently present simultaneous alterations –i.e., either low or high- responsiveness– in both systems. However, there is scarce evidence establishing whether a priori alterations in these systems –i.e., independent of previous stress exposure– may predispose to the development of psychopathologies possibly due to the lack of animal models simultaneously involving aberrant HPA and SNS responses. In this study, we describe two animal models selectively bred according to their differential (either high, 'High', or low, 'Low') glucocorticoid responsiveness to stress, in comparison to a third line of rats that displays intermediate ('Inter') glucocorticoid responses. The two extreme lines may be considered distinct models of psychopathology; the High line representing a model of constitutive mood alterations while the Low line a model of vulnerability to develop stress-induced psychopathologies. We recorded the electrocardiogram in rats from the three lines and quantified heart rate variability and vagal tone indexes during rest and stress challenges. Rats from both High and Low lines displayed higher heart rate and lower basal vagal tone than the Inter group, both at resting and following stress exposure. Specific pharmacological manipulations probing the relative contribution of sympathetic and parasympathetic components on HR modulation confirmed a relative lower vagal tone in High and Low lines and discarded differences in the sympathetic regulation of heart rate between the lines. Therefore, the two genetically-selected High and Low glucocorticoid rat lines emerge as two valuable preclinical models of psychopathology involving two key risk factors for psychiatric and cardiovascular disorders, namely dysregulations in the HPA axis and cardiac vagal functioning.